PENGARUH BAURAN PEMASARAN TERHADAP MINAT MAHASISWA KEBIDANAN MELANJUTKAN PENDIDIKAN PROFESI BIDAN DI PERGURUAN TINGGI SWASTA - Shinta Mona Lisca; Hafizzurachman Hafizzurachman (Poltekkes Kemenkes Maluku, 2021)
The Indonesian Demographic and Health Survey in 2012 showed that the Maternal Mortality Rate in Indonesia was 359 per 100,000 live births. In order to support and improve Maternal and Child Health through midwife graduates, the midwife professional study program is held. One of the factors that influence students' interest in continuing midwife professional education is the marketing mix. This research is to find out the direct and indirect effects and the magnitude of the influence of the marketing mix on the interest of midwifery students in continuing midwife professional education. The method used in this study is a quantitative approach that uses cross-sectional design. The sample used was 70 PTS midwifery students. The analytical method used is the Structural Equation Model using SmartPLS 2.0 and SPSS 20. The research findings show that student interest is directly influenced by product factors of 17,62%, price 19,97%, promotion13,19%, people 7,00% and physical 32,96%. the campus should be even more active in promoting midwife professional study programs so that students understand the importance of continuing midwife professional education.